2021
DOI: 10.1021/acs.jpca.1c09015
|View full text |Cite
|
Sign up to set email alerts
|

Cyclotrimerization of Acetylene on Clusters Con+/Fen+/Nin+(n = 1–16)

Abstract: Cyclotrimerization of acetylene to benzene has attracted significant interest, but the role of geometric and electronic effects on catalytic chemistry remains unclear. To fully elucidate the mechanism of catalytic acetylene-to-benzene conversion, we have performed a gas-phase reaction study of the Fe n + , Co n + , and Ni n + (n = 1−16) clusters with acetylene utilizing a customized mass spectrometer. It is found that their reactions with acetylene are initiated by C 2 H 2 molecular adsorption and allow for do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 94 publications
0
6
0
Order By: Relevance
“…[66a,c] Recently a gas-phase reaction study of the Fe n + , Co n + , and Ni n + (n = 1-16) clusters was conducted for the catalytic acetylene cyclotrimerization, as shown in Figure 10. [136] It was unveiled that the reactions of these metal clusters with acetylene are initiated by C 2 H 2 adsorptions, followed by rapid dehydrogenation even at low concentrations of the reactant gas acetylene; however, at high acetylene concentrations, acetylene cyclotrimerization becomes the dominant reaction channel, corresponding to the conversion of three C 2 H 2 molecules into benzene (C 6 H 6 ) facilitated by the M n + (M=Fe, Co, Ni) clusters. Quantum-chemistry calculations unveiled thermodynamicsand dynamics-favourable pathways to the formation of the M + (C 6 H 6 ) products, shedding light on the cluster catalysis and multi-molecule synergy induced by the cation-π interactions.…”
Section: Catalytic Conversion Of Hydrocarbonsmentioning
confidence: 99%
See 2 more Smart Citations
“…[66a,c] Recently a gas-phase reaction study of the Fe n + , Co n + , and Ni n + (n = 1-16) clusters was conducted for the catalytic acetylene cyclotrimerization, as shown in Figure 10. [136] It was unveiled that the reactions of these metal clusters with acetylene are initiated by C 2 H 2 adsorptions, followed by rapid dehydrogenation even at low concentrations of the reactant gas acetylene; however, at high acetylene concentrations, acetylene cyclotrimerization becomes the dominant reaction channel, corresponding to the conversion of three C 2 H 2 molecules into benzene (C 6 H 6 ) facilitated by the M n + (M=Fe, Co, Ni) clusters. Quantum-chemistry calculations unveiled thermodynamicsand dynamics-favourable pathways to the formation of the M + (C 6 H 6 ) products, shedding light on the cluster catalysis and multi-molecule synergy induced by the cation-π interactions.…”
Section: Catalytic Conversion Of Hydrocarbonsmentioning
confidence: 99%
“…Quantum-chemistry calculations unveiled thermodynamicsand dynamics-favourable pathways to the formation of the M + (C 6 H 6 ) products, shedding light on the cluster catalysis and multi-molecule synergy induced by the cation-π interactions. [136][137] Toluene to benzaldehyde. Oxidation of the well-known organic-pollutant toluene (PhÀ CH 3 ) to useful products under mild conditions is highly desirable but a challenging task.…”
Section: Catalytic Conversion Of Hydrocarbonsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous work has shown that it is possible to produce benzene from acetylene on a variety of metal surfaces under both ultra-high vacuum (UHV) and reaction conditions. 9–35 For example, Tysoe et al showed acetylene forms benzene and ethylene on a Pd(111) surface and that increasing the surface acetylene coverage increased the yield of benzene. 36 In addition, the authors observed a threshold acetylene coverage of 0.3 ML, below which benzene formation does not occur.…”
Section: Introductionmentioning
confidence: 99%
“…Metal ion–acetylene complexes have been investigated with mass spectrometry, computational chemistry, electronic spectroscopy, and IR spectroscopy. IR photodissociation spectroscopy measurements compared to the predictions of theory have provided the most detailed information about structures and bonding. Mono-acetylene complexes with a variety of metals form cation−π complexes, with metal ion binding in a symmetric position to the triple bond of acetylene. In these structures, the H–CC bond angle is changed, moving the hydrogen atoms away from the linear axis and away from the metal.…”
Section: Introductionmentioning
confidence: 99%